Kepuasan Kerja Dan Komitmen Organisasi Sebagai Faktor Penentu Loyalitas Karyawan - Muliati, Muliati; R, Masmarulan (STIM-LPI Makassar, 2025)
This study aims to examine the effect of satisfaction and commitment on employee loyalty at Grand Toserba Makassar. The population in this study were all employees of Grand Toserba Makassar. Sampling using purposive sampling method, namely only employees at Grand Toserba Jln. Pengayowan City of Makassar. totaling 30 people. This study found that there is a positive and significant effect of satisfaction and commitment on employee loyalty. The largest correlation occurs between satisfaction of 0.691 on loyalty, and the correlation of commitment to employee loyalty of 0.625. Partially, satisfaction has a t-count value of 2,712, and commitment has a t-count value of 2,562, both t-counts are greater than t-table, this means that satisfaction and commitment partially have a significant positive effect on employee loyalty. This finding shows that high job satisfaction is often the basis for building long-term commitment. When employees are satisfied, they are more open to emotional and professional engagement, which increases their commitment to the company. This synergy between satisfaction and commitment creates strong and sustainable loyalty.